Collective Immune Defense Achieved Through Widespread Exposure and Immunization in Populations - Shafqat Rasool; Muhammad Imran; Fahad Said Khan; Nosheen Naseem; Rabia Anum*; Imtiaz Mahmood Tahir*; Muhammad Akhlaq; Aasma Ahsan; Iftikhar Younis Mallhi; Muhammad Shakeel; Rimsha Zainab; Shah Mulk; et al. (Dialogue Social Science Review (DSSR), 2025)
The attainment of herd immunity is a critical factor in mitigating epidemics and safeguarding vulnerable populations, such as young children, the elderly, or immunocompromised individuals, who may not be eligible for vaccination or unable to develop immunity due to health constraints. The extent of herd immunity required is determined by the interplay between the infectious agent's transmissibility and the population's immunity, which can be acquired either through vaccination (artificial immunity) or natural infection (natural immunity). Vaccination is generally considered the most ethical and efficient method for achieving herds immunity, as it eliminates disease-related risks and mortality. Factors influencing the efficiency of herd immunity include the basic reproduction number (R₀) of the pathogen, vaccination coverage, community immunological response, and public health interventions. The required immunity levels for achieving herd immunity vary by disease, with higher R₀ pathogens necessitating a larger proportion of the population to be immune. For example, nearly 95% of the population must be immune to prevent the spread of measles, which has an R₀ of 12 to 18. While herd immunity is crucial, it is not a standalone solution. Its success depends on multiple determinants, such as social behavior, public health infrastructure, and vaccine accessibility. Additionally, the emergence of new pathogen variants (e.g., in COVID-19) poses a risk to herd immunity when immunity derived from previous infections or vaccinations is excluded. Therefore, herd immunity should be integrated into a comprehensive public health strategy encompassing surveillance, response, and disease prevention Keywords: Immunity threshold, Infection spread, International health, Infection control, Fragile communities